Pengaruh Group Therapy Reminiscence terhadap Subjective Well Being pada Lansia di Posyandu Bina Sehat Desa Donohudan, Boyolali - Mila Cahyani Putri, Fariska; Sri Wahyuni, Endang (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Backgroud: Physical, social, and emotional changes in the elderly can affect subjective well-being. High and low SWB of the elderly affects happiness and life satisfaction. To achieve optimal SWB, the elderly can be stimulated by remembering past experiences with reminiscence therapy. Objectives: This study aims to determine the effect of reminiscence group therapy on SWB in the elderly in Bina Sehat Integrated Servive Post Donohudan Village, Boyolali. Methods: This study used the Pre-Experiment method with One Group Pretest- Posttest Design. Sampling used purposive sampling according to the inclsioncriteria set b he researcher. Data analysis was performed with SPSS 25. Results: Respondents in this study amounted to 23 (100%) elderly with predominantly elderly (60-74 years) as many as 19 (82.6%). Respondents female as many as 23 (100%). The last education was dominated with elementary school, namely 17 (73.9%) elderly. A total of 16 (69.5%) elderly do not work. In the Wilcoxon test results, the p value is 0.001, which means that there is a difference in subjective well-being towards reminiscence group therapy. Conclusion: This study shows that group therapy reminiscence affects the SWB of the elderly in Bina Sehat Integrated Servive Post Donohudan Village, Boyolali Regency. Keywords : Elderly, Reminiscence Group Therapy, Subjective Well-being